2015
DOI: 10.1111/2041-210x.12404
|View full text |Cite
|
Sign up to set email alerts
|

Discrete choice modelling of natal dispersal: ‘Choosing’ where to breed from a finite set of available areas

Abstract: Summary1. Classic natal dispersal studies focus mainly on distance travelled. Although distances capture some of the main selective pressures related to dispersal, this approach cannot easily incorporate the properties of the actual destination vs. the available alternatives. Recently, movement ecology studies have addressed questions on movement decisions in relation to availability of resources and/or availability of suitable habitats through the use of discrete choice models (DCMs), a widely used type of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 54 publications
(114 reference statements)
1
17
0
Order By: Relevance
“…We used discrete choice models similar to Vardakis et al. () for considering dispersal as a choice process whereby individuals’ decisions are ruled by the characteristics of the chosen patch and of alternative choices. Using this relatively novel methodological approach, and utilising dispersal data from mink recolonising a large area repeatedly depleted of conspecifics by culling implemented by volunteers, we provided evidence of both density dependence and habitat quality affecting mink settlement decisions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We used discrete choice models similar to Vardakis et al. () for considering dispersal as a choice process whereby individuals’ decisions are ruled by the characteristics of the chosen patch and of alternative choices. Using this relatively novel methodological approach, and utilising dispersal data from mink recolonising a large area repeatedly depleted of conspecifics by culling implemented by volunteers, we provided evidence of both density dependence and habitat quality affecting mink settlement decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Dispersal movement data have recently been analysed using multinomial discrete choice models (multinomial regression models), where the probability of settling in a particular patch is a function of patch‐ and individual‐level covariates (Vardakis et al., ). We used multinomial probit models to describe individuals’ choice from a finite set of mutually exclusive alternatives.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature about discrete choice models is very extensive (Hensher and Johnson, 2018;Louviere and Woodworth, 1983;McFadden, 1986;Ben-Akiva and Boccara, 1995;McFadden and Train, 2000;Louviere et al, 2000;Hensher et al, 2005) and applications can be found in marketing (Kamakura and Russell, 1989), environmental economics (Bennett and Blamey, 2001), transport (Kupfer et al, 2016), health care (Lancsar and Louviere, 2008;Luyten et al, 2015), ecology (Vardakis et al, 2015) and many other disciplines. However, in the analysis of choice data, products that are mixtures of ingredients have been largely overlooked.…”
Section: Introductionmentioning
confidence: 99%